Changing Needs for Information and Support in an Online System for Parents of Children With Kidney Disease. Issue 1 (22nd June 2017) - Pinsk, Maury; Nicholas, David
Background: Pediatric chronic kidney disease is psychologically, financially, and physically demanding on parents providing care. Parents often feel isolated because of the rarity of the condition, and geographic isolation often compounds this perception in Canada. Many parents seek assistance online for both information and social support. Objective: This study examines an online portal, titled "Ability Online, " which was designed to provide support and information to a diverse group of parents using chat facilities, bulletin boards, and e-mail. Specifically, we sought to identify how the technologies offered in this system related to the support and information seeking needs for parents. Secondary aims of determining possible reasons for attrition over time were explored as well. Design: Mixed methodology sequential exploratory design using the qualitative methodology of descriptive interpretation. Setting: Telephone interviews. Patients: Twenty parents of pediatric patients with chronic kidney disease from four Canadian centers who engaged in an online social support system "Ability Online." Measurements: Interview transcripts generated from 20 taped phone conversations were reviewed from parents who engaged in the online system, and the themes derived from these transcripts served to generate semistructured interview questions that focused on their use of, and perceived benefit from, this technology for social support. Follow-up telephone interviews were then conducted with a 6-person subset of the original group in an effort to further define the impact of technology on their experience. This same smaller cohort provided data on social supports, caregiver satisfaction, and caregiver stress. Results: Many parents experience a progression through which their needs for knowledge and support change over time. Specifically, parents describe a transition from pure information seeking, to seeking parental interaction, mutual support and collaboration, and ultimately to advocacy. Parents described how technology could be used to address those needs. Limitations: Our cohort was slightly more educated and representative of more urban populations than published data reflecting the population of North American pediatric patients living with kidney disease. Conclusions: Our data suggest themes of technology use influencing the goals of online support seeking. While our findings are preliminary, further study may inform Web designers to identify the changing needs of participants in designing such online support networks, and minimize the reasons that participants fail to adopt, or terminate their online experiences.